A percepção do papel da universidade no desenvolvimento tecnológico e na inovação sob a ótica de políticas governamentais e sua prática - Soll, João Climaco Borba (2009)
This study aims to investigate the relationship between the mechanisms provided by the Brazilian government policies to simulate technological development and innovation and the practice of the universities. From the point of view of its nature, it is an applied research. Regarding it's goal, it's exploratory research. With regard to technical procedures, it uses research literature, documentary research and field research. Two universities were selected: UTFPR (Federal Technological University of Paraná) and PUC-PR (Pontifical Catholic University-Paraná), in their campus in Curitiba-Pr where the data collection and analysis were realized. In general, the results showed that in the university-companies cooperation process, the universities can be presented in joint, revealing similarities between them. The results pointed that the public policies to encourage innovation focus on the transformation of the university as the main conductor of technological development.